Evaluación de 4 casos de dengue con signos de alarma que ingresaron; hospital básico huaquillas periodo enero - diciembre 2016 - Siguenza Murgueitio, Jairo Michael (2018)
Dengue is a viral infection: produced by the virus (DENV), which belongs; the family Flaviviridae contains five different serotypes (DEN V1-5), it is transmitted through the bite of a mosquito (Aides aegypti) which is distributed worldwide; but it has predominance in urban and peri-urban areas, the habits of the vector are: to show preference for places close to the human being, lives in containers that contain clean water, which reproduces inside them and around their homes. The annual incidence of this viral infection reaches up to 50 million cases per year, of which 500,000 people are hospitalized and 20,000 people die. The most characteristic symptoms are thermal elevation, retro ocular pain, facial ruddiness, skin erythema, arthralgia, myalgia and in severe cases abdominal pain, persistent vomiting, irritability-lethargy, mucous bleeding, fluid accumulation, hepatomegaly. Dengue is classified according to degrees of severity: Dengue without warning signs: presented the following clinical manifestations arthralgia, myalgia, thermal rise, nausea, vomiting, rashes, and should be endemic area, dengue with warning signs: may present the same clinical manifestations as the previous case, adding abdominal pain, extravasation of fluids; severe dengue: it presents clinical manifestations: shock, respiratory difficulty, mucous membrane hemorrhage or severe organ damage. The treatment is based mainly on the symptomatology of the patient, those patients diagnosed with dengue without warning signs the treatment consists of oral serum of 2 to 3 ml / kg; if there are signs of alarm, the treatment is based on hydration with isotonic solutions (saline 0.9%) of 5-7 maximum 10 ml / kg; if the diagnosis is dengue, severe dengue is hydrated 10-20 ml / kg, blood, platelets, etc. are administered if necessary. To establish the diagnosis of dengue it is important to take into account differential diagnoses, especially in the pediatric population, which cause a lot of confusion when making the diagnosis. Among these, we have pathologies that most often occur in the pediatric age as Urinary Tract Infection, where the symptomatology is similar to that of dengue fever with thermal upwelling and malaise, it must be supported by complementary tests to establish its diagnosis; Infection of upper respiratory tracts of viral origin whose clinical picture consists of, thermal rise, irritability, arthralgia, myalgia, lethargy, a picture similar to that of dengue, diagnosis is clinical and autoimmune hepatitis has nonspecific symptoms: weight loss, anorexia and decay, the diagnosis is made by laboratory transaminase levels are elevated. In the present research work is made the analysis of several clinical cases that were presented in the Basic Hospital of Huaquillas where several patients with dengue were diagnosed in their different types, who remained hospitalized under that diagnosis, complementary tests were carried out and diagnosis of more frequent pathologies in childhood as urinary tract infection, acute respiratory tract infection, and one of the hospitalized cases ends in the severe complication of infection caused by dengue; in some cases differential diagnosis is made and in others the diagnosis is incomplete or erroneous.